Late Holocene intermediate water variability in the northeastern Atlantic as recorded by deep-sea corals - Copard, K; Colin, C; Henderson, G; Scholten, J; Douville, E; Sicre, M; Frank, N (2012)
The Nd isotopic composition of the aragonite skeleton of fossil deep-sea corals (Lophelia pertusa, Madrepora oculata and Desmophyllum dianthus) located in the northeastern Atlantic at water depths between 635 and 1300. m was investigated to reconstruct changes in the Atlantic mid-depth gyre circulation during the past millennium. The coral εNd values varied systematically from - 11.8 to - 14.4 during the past 1500. years, reflecting variations in seawater εNd and thus water mass provenance. Low εNd values (εNd = - 14) occurred during the warm Medieval Climatic Anomaly (MCA) (between 1000. AD and 1250. AD) and during the most recent period (1950. AD to 2000. AD), interrupted by a period of significantly higher εNd values (~-12.5) during the Little Ice Age (LIA) (between 1350. AD and 1850. AD). One long-lived branching coral even recorded an abrupt systematic rise from low to high εNd values around 1250. AD over the course of its 10-year growth period.These variations are interpreted to result from variable contributions of the subpolar and subtropical Atlantic intermediate water masses, which today are characterized by εNd values of - 15 and ~-11, respectively. The low εNd values observed during the warm MCA and during recent times imply a strong eastward extension of the mid-depth subpolar gyre (SPG) induced by a dominant positive phase of the North Atlantic oscillation (NAO). During the LIA, water from the subtropical gyre (STG) and potentially from the Mediterranean Sea Water (MSW) propagated further northward, as indicated by the higher coral εNd values. This pattern suggests a negative mean state of the NAO during the LIA, with weaker and more southerly located Westerlies and a westward contraction of the SPG. Variations in the contributions of the two gyres imply changes in the heat and salt budgets at intermediate depths during the past millennia that may have contributed to changes in the properties of North Atlantic inflow into the Nordic Seas and thus deep-water formation. © 2011 Elsevier B.V.